A MIXED COHORT STUDY ON DIETARY ADHERENCE, INFECTION PREVENTION, AND GLYCEMIC CONTROL AMONG DIABETIC PATIENTS IN SOUTH KIVU, EASTERN DEMOCRATIC REPUBLIC OF THE CONGO. - MORISHO, Lambert; Charles, BAMAVU AMISI; Serge, CHIRIMWAMI MUGANDA; Elie, BAHOGWERHE KASHENGULA; morisho, mwala; Bertin, KIPINDULA MORISHO (Student's Journal of Health Research Africa, 2025)
Background Diabetes is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body does not use it effectively. A well-adapted diet is essential to stabilize blood glucose levels and prevent complications such as hyperglycaemia and infections. However, adherence to this diet is often compromised by socio-economic factors, limiting access to balanced nutrition and healthcare. This study aims to evaluate the impact of dietary adherence on diabetes management, focusing on infection prevention and glycaemic control. Materials and Method A longitudinal study (2020-2024) in South Kivu (Bukavu, Mwenga, Walungu) followed diabetic patients. After informed consent, data was collected through medical records and structured interviews using standardized forms. Statistical analyses, including chi-square tests and logistic regressions, were performed using Jamovi software. Results Among 1520 patients, 59.3% of those with stable blood glucose levels adhered to the diet, with an infection rate of 56.8%, compared to 81.9% for non-adherent patients. Among patients with unstable blood glucose levels, 16.5% adhered to the diet, with an infection rate of 27.2%, compared to 98.1% among non-adherent patients. Non-adherence was associated with a higher risk of infection (OR = 7.84), hyperglycaemia (OR: 4.6), hospitalisation (OR = 2.03), and comorbidities (OR = 4.8). Conclusion Dietary adherence plays a crucial role in diabetes management by reducing infections and improving glycaemic control. Recommendations However, socioeconomic constraints have a significant impact on adherence. Strengthening nutrition education and improving access to healthcare, especially in rural areas, are essential strategies to optimize diabetes management and reduce associated complications.